Association of Axial Length and Myopia Degree: A Retrospective Study - Syena Damara; Ani Ismail (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Myopia is a clinical condition that occurs when the image of a distant object is focused in front of the retina by the non-accommodating eye. The prevalence of Myopia has been getting higher for decades. A cohort study stated continuing axial elongation in adults with high Myopia. Methods: This research is a retrospective study approach. Data obtained from central general hospital Dr. Mohammad Hoesin Palembang from January 2021 to February 2022. Medical record data included in this study were patients diagnosed as myopic patients. The exclusion criteria were patients with missing medical records and any other refractive disorder. The correlation between myopia degree and axial length using ANOVA or Kruskal-Wallis H test depend on its data distribution. Data processing was performed using SPSS version 25. This study aims to determine the association between axial length and myopia degree. Results: Female patients are found predominantly (58.5%). Through the recent surveys, either the domestic or foreign population, results have stated that the prevalence of Myopia is higher in females, and other studies found that it fluctuated with age among adolescent females. The age of patients varies from 16 years to 75 years, and the mean baseline is 30.9± 3.82 years. Mild Myopia accounts most common incidence (53.1%), with laterality, which is found to be more common in the left eye (57.1%). Mean baseline axial length 21.95± 2.85 with visual acuity in LogMar 0.89 ± 0.51. There is a statistically significant difference in axial length based on myopia degree (p=0.000). Conclusion: Female patients are found predominantly in myopia patients, with the age of patients varying from 16 years to 75 years and a mean baseline of 30.9± 3.82 years. There is a statistically significant difference in axial length based on myopia degree.